A generalization of the boundedness of certain integral operators in variable lebesgue spaces - Urciuolo, Marta (2020)
Let n ε N. Let A1, ...Am be n×n invertible matrices. Let 0 ≤ α < n and 0 < αi < n such that α1 +...+αm = n-α . We define In [8] we obtained the boundedness of this operator from Lp(.)(Rn) into Lq(.)(Rn) for 1/q(.) = 1/p(.) - α/n, in the case that Ai is a power of certain fixed matrix A and for exponent functions p satisfying log-Hölder conditions and p(Ay) = p(y), y ε Rn. We will show now that the hypothesis on p, in certain cases, is necessary for the boundedness of Tα and we also prove the result for more general matrices Ai.